CONDITIONS FOR PRIMARY PRODUCTION OF PHYTOPLANKTON IN THE VOSTOK BAY (JAPAN SEA) IN SPRING 2016 - P. P. Tishchenko; P. Ya. Tishchenko; O. A. Elovskaya; V. I. Zvalinsky; Yu. V. Fedorets (Известия ТИНРО, 2019)
The Vostok Bay was surveyed on March 16–18, 2016 with measuring of water properties profiles by oceanographic sondes Sea-Bird SBE-19plus V2 and Rinko Profiler ASTD-102 with sensors of pressure, temperature, conductivity, turbidity, chlorophyll fluorescence, dissolved oxygen, and photosynthetically active radiation (PAR) and collecting of water samples by SBE-32 carousel sampler with 10 liter bottles for further measuring of nutrients (P, Si and N in forms of nitrate and ammonium) and chlorophyll a concentration and phyto- and zooplankton abundance and species composition. Assimilation number (Pb ) of phytoplankton was determined using the optical sensor of dissolved oxygen mounted on logger Rinko AR01-USB and primary production was calculated from the measured values of Pb , Chl a and PAR. Values of primary production ranged from 200 to 2100 mgC/(m2.day). The highest phytoplankton growth was detected at the depth of 8–10 m in the northern Vostok Bay and 10–16 m in its southern part. The total daily production of phytoplankton within the Bay was estimated as 12.5 tC. Species composition of phytoplankton was formed mainly by diatoms (Bacillariophyta) and dinophytes (Dinophyta). The highest biomass of raw phytoplankton was registered at the sea surface, whereas the highest values of chlorophyll concentration occurred mainly at the bottom of the bay. Species composition of zooplankton was typical for spring season, with domination of copepods presented mainly by neritic species; its biomass was in 12 times lower than the phytoplankton biomass, on average. There was concluded that photosynthetic activity of phytoplankton was limited by nitrate availability, therefore it was intensified by penetration of relatively cold, nitrogen-rich waters from the deep-water sea to the Vostok Bay.